2020
DOI: 10.9734/acri/2019/v19i430161
|View full text |Cite
|
Sign up to set email alerts
|

Niche-proxies of Hydrocarbon-impacted Rhizosphere Soil of Weeds of Bodo in Gokana, Rivers State, Nigeria

Abstract: Niche-ecology and isolation studies of microbes from the environment have been described as the bedrock and driving-force for bioprocess industry. This investigation was designed to determine the microbiological quality of weeds growing on aged-crude oil polluted soil.  Ten (10) weeds Cyperus esculentus, Scleria pauciflora. Asystasia gangetica Harungana madagascariensis, Ancistoclaudus tectorius, Kyllinga erecta, Cinna arundinacea, Brassica chinensis, Cyperus difformis, Kyllinga bulbosa and Brachiaria mutica a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Uquetan et al [36] have identified the influence of crude oil and hydrocarbons on crop productivity and yield. They emphasize that hydrocarbons within crude oil-contaminated soil disrupt the soil's physical, chemical [37], and microbiological [13,[38][39][40] properties. These disruptions significantly contribute to diminished crop productivity, particularly impacting the functional roles of soil organisms.…”
Section: Pollution Of Environmental Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Uquetan et al [36] have identified the influence of crude oil and hydrocarbons on crop productivity and yield. They emphasize that hydrocarbons within crude oil-contaminated soil disrupt the soil's physical, chemical [37], and microbiological [13,[38][39][40] properties. These disruptions significantly contribute to diminished crop productivity, particularly impacting the functional roles of soil organisms.…”
Section: Pollution Of Environmental Mediamentioning
confidence: 99%
“…A wide array of organic waste holds potential for bioenergy production and serves as a medium amendment for cultivating valuable resources. The ascendancy of agrowaste as feedstocks and substrates for microbial product synthesis underscores their capacity to provide essential nutrients [40,47]. Biotechnological applications leverage agro-waste for nutrient supply in biostimulation processes, as immobilization matrices for starter cultures or inocula, and as supplements for lipid biosynthesis [48].…”
Section: Agro-waste As Substrates For Bioremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten-fold serial (10-fold) using sterile distilled water as a diluent. Cultured plates were counted for visible colonies and presented in CFU/ml (Effiong et al, 2020).…”
Section: Determination Of Total Fungal Count (Tfc)mentioning
confidence: 99%